PEDOT coated iron phosphide nanorod arrays as high-performance supercapacitor negative electrodes. Issue 7 (8th January 2018) - Luo, Jinling; Zheng, Zhi; Kumamoto, Akihito; Unah, Winifred Ini; Yan, Shuke; Ikuhara, Yumi H.; Xiang, Xia; Zu, Xiaotao; Zhou, Weilie
Abstract : PEDOT coated iron phosphide nanorod arrays are synthesized and exhibit high areal specific capacitance and significantly improved cycling stability as negative electrodes for supercapacitors. Abstract : PEDOT coated iron phosphide nanorod arrays are synthesized and demonstrated as high-performance negative electrodes for supercapacitors with high areal specific capacitance and significantly improved cycling stability. A MnO2 //FeP/PEDOT aqueous asymmetric supercapacitor is fabricated with a high volumetric capacitance of 4.53 F cm −3 and an energy density of 1.61 mW h cm −3 .